Предмет: Математика,
автор: Аноним
Помогите пожалуйста
Помоогитеее
Приложения:
Ответы
Автор ответа:
1
Ответ:
9.8 - (5,6-2х) - (1,2+х)
Автор ответа:
1
Ответ:
В решении.
Пошаговое объяснение:
9,8 - (5,6 - 2х) - (1,2 + х) = 3 + х
9,8 - (5,6 - 2х) - (1,2 + х) =
= 9,8 - 5,6 + 2х - 1,2 - х =
= (9,8 - 5,6 - 1,2) + (2х - х) =
= 3 + х;
3 + х = 3 + х, верно.
Похожие вопросы
Предмет: Русский язык,
автор: andrey555218
Предмет: Русский язык,
автор: Arabica150602
Предмет: Английский язык,
автор: NecoNico123
Предмет: Английский язык,
автор: shestopal723
Предмет: Химия,
автор: Neizvestnaya37